A study on the impact of diet supplementation of fermented dried seaweed powder (Kappaphycus alvarezii) on healthy cat gut performance, skin and hair coat conditions, and behaviour - Mohamad Yusof, Loqman; Ahmad, Hafandi; Abu Hassim, Hasliza; Mustaffa-Kamal, Farina; Omar, Sharina; Zainundin, Nur Karmila; Padam, Birdie Scott (Springer Science and Business Media, 2024)
One of the key goals the feed industry emphasizes when exploring the incorporation of novel substances into animal diets is to enhance feed utilization efficiency, to bolster animal health and well-being. Fermented seaweed powder holds promise as a valuable and sustainable component of animal feed, owing to its rich nutrient profile and purported benefits for livestock and aquaculture species. This study provides some interesting and original preliminary data regarding the benefits of supplementing cats’ diets with fermented dried seaweed. Using a broad investigative approach to measure and analyse multiple health benefits of feeding fermented dried macroalgae to cats as a nutritional supplement, the results of this 8-week study identified several positive health attributes related to body coat quality, nutrient digestibility, behavioural changes, a healthy gut microbiota ratio, and enhanced immunity. There were no adverse effects observed in the cats after supplementation with the fermented seaweed powder. The sample size in this study with cats should be increased, but this preliminary work showed that the seaweed-supplemented cats exhibited improvements in the measured health parameters over the control cats. As a result of this 8-week trial, key information has been provided regarding future research direction focusing on skin health application which is essential to the overall animal wellbeing.